2016
DOI: 10.1590/1980-5497201600010018
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome and alcohol consumption in prison employees

Abstract: Men who smoke were more likely to develop an at-risk drinking pattern, while religion is presented as a protective factor. Individuals who consume alcohol were more affected by the different factors of the Burnout Syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
3
12
1
1
Order By: Relevance
“…In the case of mean comparisons, it was found that correctional officers who experienced a burnout (model A) and burnout + PD (model B) showed: riskier frequencies of alcohol consumption (higher) and physical activity (lower) in the case of model A, and a riskier frequency of alcohol consumption (higher), overweight rates (higher) and social support (lower) for model B. In short, it is important to highlight some relevant findings of this research for what concerns this: first, that both a higher level of alcohol consumption and the fact of being overweight (and other health issues) were related to more psychosocial hazards at work, especially among workers belonging to high-risk professions such as prison-related ones [28,33,79]; and secondly, that other studies have related job stress and burnout to lower rates of social support, and have remarked the importance of strengthening co-workers’ support as a way of coping with adverse factors at the workplace [16,20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of mean comparisons, it was found that correctional officers who experienced a burnout (model A) and burnout + PD (model B) showed: riskier frequencies of alcohol consumption (higher) and physical activity (lower) in the case of model A, and a riskier frequency of alcohol consumption (higher), overweight rates (higher) and social support (lower) for model B. In short, it is important to highlight some relevant findings of this research for what concerns this: first, that both a higher level of alcohol consumption and the fact of being overweight (and other health issues) were related to more psychosocial hazards at work, especially among workers belonging to high-risk professions such as prison-related ones [28,33,79]; and secondly, that other studies have related job stress and burnout to lower rates of social support, and have remarked the importance of strengthening co-workers’ support as a way of coping with adverse factors at the workplace [16,20].…”
Section: Resultsmentioning
confidence: 99%
“…According to the evidence, workers in different industries that experience burnout symptoms normally require the occupational implementation of programs and/or complex organizational strategies [6], in order to improve their way of coping with several comorbid factors, such as job stress [24,25], chronic fatigue and sleep problems [26], addictive behaviors [27,28], and different mid/long-term health complains [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some similar associations of predictors with burnout were identified in other occupational studies. Thus, alcohol use was shown to have a positive association with burnout in intensive care physicians [6], community pharmacists [7], prison employees [8], priests [9], and similar association was found in a populations-based sample [10]. Since data on firefighters on such association were not published before, findings from the latter population-based study assume that such association is not specific for firefighters and can be found in many other occupations.…”
Section: Discussionmentioning
confidence: 99%
“…Bolat et al reported that smoking urologists experienced higher levels of burnout than non-smoker urologists [25]. Campos et al revealed that prison employees with alcohol consumption had higher burnout levels than sober ones [26]. The prevalence of smoking habit among the bank employees participating in the study was 41.0%.…”
Section: Discussionmentioning
confidence: 81%